Assessing the Needs of Our Students: Using a Course Rotation Cycle to Increase Well-Being - DiTunnariello, Nancy (Pedagogika Społeczna Nova, 2025)
In an effort to better understand how a decrease in university enrollment has led to a series of campus closures across the United States, this paper of practice proposes a structural change to assist students and departments alike. Using an action research approach and a case study-like format, the author takes a closer look at two departments at St. John’s University, Staten Island, New York, USA to better understand the problem, and propose a potential solution in offering a four-year course cycle to assist in cutting costs and meeting student needs. This practice paper highlights the pedagogical practice of a mainly two-year institution to provide relevant insights into what went wrong with the university system. The paper layout includes a literature review highlighting the current state of enrollment concerns in the United States, a closer look at the university in question, an explanation of how Maslow’s Hierarchy of Needs can be used as a lens for showcasing universit.